Consumptive Behaviour in the Digital Era: The Influence of E-Commerce, Hedonic Lifestyle, and Peer Conformity - Putri Rahayu; Muhammad Yafiz; Purnama Ramadani Silalah (Jurnal Bisnis dan Manajemen, 2026)
This study aims to analyze the influence of e-commerce, hedonic lifestyle, and peer influence on the consumptive behavior of students at the State Islamic University of North Sumatra. This research employs a quantitative method with an associative approach. The population of this study consists of students at the State Islamic University of North Sumatra, with a sample of 140 respondents selected using proportional random sampling. Data were collected through Likert-scale questionnaires and analyzed using validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis with the assistance of SPSS 26. The results show that the correlation coefficient (R) is 0.76, indicating a positive and moderately strong relationship among the research variables, while the coefficient of determination (R²) of 0.58 indicates that 58% of students’ consumptive behavior can be explained by e-commerce, hedonic lifestyle, and peer influence. Partially, e-commerce (6.403 > 1.977), hedonic lifestyle (4.214 > 1.977), and peer influence (2.673 > 1.977) have a positive and significant effect on the consumptive behavior of students at the State Islamic University of North Sumatra. E-commerce is the most dominant factor influencing students’ consumptive behavior. These findings indicate that students’ consumptive behavior is influenced by technological factors, lifestyle orientation, and social environment, highlighting the importance of financial awareness to encourage more rational spending behavior.